2021
DOI: 10.3390/condmat6040052
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Charge-Lattice Dynamics across the Kuramoto Synchronization Phase Diagram of Quantum Tunneling Polarons in Cuprate Superconductors

Abstract: Because of its sensitivity to the instantaneous structure factor, S(Q,t = 0), Extended X-ray Absorption Fine Structure (EXAFS) is a powerful tool for probing the dynamic structure of condensed matter systems in which the charge and lattice dynamics are coupled. When applied to hole-doped cuprate superconductors, EXAFS has revealed the presence of internal quantum tunneling polarons (IQTPs). An IQTP arises in EXAFS as a two-site distribution for certain Cu–O pairs, which is also duplicated in inelastic scatteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…These experimental and theoretical results provide a critical extension to our prior EXAFS studies that demonstrated that the two-site Cu-O distributions in the dynamic structure that constitute the IQTPs are strongly coupled to the HTSC [6,8,12,13,19,30,31] as well as these overdoped, superconducting SCO and YSCO-Mo [57]. It would be expected that a phenomenon that is coupled to the HTSC mechanism would exhibit a correlation with T c .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…These experimental and theoretical results provide a critical extension to our prior EXAFS studies that demonstrated that the two-site Cu-O distributions in the dynamic structure that constitute the IQTPs are strongly coupled to the HTSC [6,8,12,13,19,30,31] as well as these overdoped, superconducting SCO and YSCO-Mo [57]. It would be expected that a phenomenon that is coupled to the HTSC mechanism would exhibit a correlation with T c .…”
Section: Discussionsupporting
confidence: 60%
“…The minimal subunit encompassing the relevant constituents consists of a pair of neighboring Cu-Oap IQTPs bridged between their copper ions by an Opl and between their Oap by the strontium of the dielectric layer (figure 1) [30,31]. The novel aspects enabled by this structure are the addition of the CuO 2 plane through the inclusion of Opl and the anharmonic structural dynamics of the Cu-Sr pair that is incorporated via the nontrivial Oap-Sr-Oap triatomic molecular structure indicated by these EXAFS results.…”
Section: Model Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Kuramoto model is the most important classical model displaying this phase transition. The model has been successfully used to describe arrays of coupled Josephson junctions [123] and recently is gaining further attention for study of condensed matter phenomena such as persistent entanglement in isolated quantum systems, exciton delocalization in molecular aggregates, and tunneling of polarons in cuprate superconductors [124][125][126].…”
Section: Phase Transitions and Collective Phenomenamentioning
confidence: 99%